Static halogen battery based on multi-electron transfer mechanism

By introducing chloride ionic liquids as electrolyte additives in halogen batteries, the reversible conversion of high-valent halogen ions is achieved, solving the problem of low multi-electron conversion efficiency of existing halogen batteries, and significantly improving the energy density and energy output characteristics of the battery.

CN119786761APending Publication Date: 2025-04-08ZHENGZHOU UNIV

Patent Information

Application Number
CN202411991148.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing halogen batteries have problems such as complex system, low efficiency, poor reversibility, insufficient conversion, and dynamic hysteresis in multi-electron conversion, resulting in low capacity, low voltage, and low energy density, making it difficult to meet the actual application needs.

Method used

Using a static halogen battery based on a multi-electron transfer mechanism, the high-valent halogen ions I+ and/or Br+ are stably generated by adding chloride ionic liquid to the electrolyte as an additive, thereby achieving its reversible transformation in various electrolyte systems.

Benefits of technology

The discharge platform, discharge capacity and energy density of halogen batteries have been significantly improved. Especially in bromine battery systems, the energy output characteristics are optimized, and the electrolyte additive has green and gentle characteristics, protecting the negative electrode structure and preventing corrosion of the battery packaging components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786761A_ABST
    Figure CN119786761A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemical energy storage batteries, and discloses a static halogen battery based on a multi-electron transfer mechanism, the halogen battery comprises a positive electrode, an electrolyte, a negative electrode, a diaphragm and a packaging material, according to the static halogen battery provided by the invention, the chloride ionic liquid is used as an electrolyte additive, high-valence halogen ions I < + > and / or Br < + > can be stably generated, and reversible conversion of the high-valence halogen ions in various electrolyte systems is successfully realized; compared with a traditional single-electron-mechanism halogen battery, the discharge platform, the discharge capacity and the energy density of the halogen battery under a multi-electron transfer mechanism can be multiplied, and particularly, the energy output characteristic of the battery is remarkably optimized for a bromine battery system with a higher discharge platform # imgabs0 #.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrochemical energy storage batteries, in particular to a static halogen battery based on a multi-electron transfer mechanism. Background Art

[0002] In the past few decades, driven by the widespread demand of the electric vehicle industry and grid energy storage, rechargeable batteries with higher energy density and sustainability have been widely studied. Different from traditional rocking chair batteries or batteries with embedded mechanisms, conversion batteries can achieve reversible transfer of multiple electrons by virtue of the rich transitions between different ion valence states, and have higher discharge capacity and energy density. Among them, compared with conversion-type positive electrode materials such as sulfur (S), selenium (Se), and tellurium (Te), halogens have higher theoretical redox potentials and more electron transfer potential, which brings higher discharge voltage and higher energy density to halogen batteries.

[0003] At present, the public technology is based on the inefficient single electron X - / X 0 (X=I, Br) reaction mechanism is used as the power supply pathway. The entire reaction is achieved through the reversible transformation of halogen substances between -1 valence and 0 valence, realizing the reversible transfer of only a single electron, resulting in low discharge capacity, low discharge voltage and low energy density. The presence of high-valent halogen ions in existing electrolytes is unstable and faces the risk of irreversible transformation, which poses a challenge to the multi-electron transfer of halogens. In the public technology, there is a proposal based on Lewis acid-base theory to use highly electronegative chloride ions as initiators, and to form halogen inter-compounds ICl at high potentials by using chemical bonds, thereby anchoring high-valent halogen cations and realizing reversible conversion of high-valent halogen cations. Liang Xiao's team at Hunan University and others realized I by adding inorganic chloride salts to the electrolyte. - / I 0 / I + and / or Br - / Br 0 / Br + However, the current multi-electron conversion of high-valent halogen ions has problems such as complex system, low efficiency, poor reversibility, insufficient conversion, and kinetic hysteresis, which leads to low capacity, low voltage, and low energy density of halogen batteries, which is far from the theoretical performance and difficult to meet the needs of practical applications. Summary of the invention

[0004] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a static halogen battery based on a multi-electron transfer mechanism.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A static halogen battery based on a multi-electron transfer mechanism comprises a positive electrode, an electrolyte, a negative electrode, a separator and a packaging material, wherein a chloride ion liquid is used as an additive in the electrolyte.

[0007] Preferably, the positive electrode comprises a positive electrode halogen active material, a conductive agent, a binder and a current collector.

[0008] Preferably, the positive electrode halogen active material includes: iodine element, bromine element, iodide and bromide and iodine / bromine mixed halide, wherein the positive electrode halogen active material includes one or more of inorganic halides, halogen-containing perovskite materials, organic molecular halides, two-dimensional transition metal carbides / borides of halogen terminal groups, and halogen-containing ionic liquids as iodine and / or bromine sources.

[0009] Preferably, the inorganic halide includes iodine, bromine, tin tetraiodide, ruthenium iodide, silver iodide, lead iodide, antimony iodide, zinc iodide, tellurium tetraiodide, cuprous iodide, bismuth triiodide, tin bromide, ruthenium bromide, silver bromide, lead iodide, antimony bromide, zinc bromide, tellurium tetrabromide, cuprous bromide, bismuth tribromide and a mixed halogen compound iodine bromide.

[0010] Preferably, the halogen-containing perovskite material includes tin-based iodine-rich perovskite (ODASnI4, wherein ODA is 1,8-octanediamine), lead-based iodine-rich perovskite (CsPbI3), lead-based bromide-rich perovskite (FAPbBr3, wherein FA is formamidine), CsPbCl3-xBr x , and mixed halide perovskites such as MAPb(Br x I 1-x )3.

[0011] Preferably, the organic molecular halide includes methylammonium iodide (MAI), trimethylammonium iodide (MAI3), ethyl viologen diiodide (EVI2), 2,4,6-triiodophenol, tetrapropylammonium tribromide (TPABr3), ethyl viologen dibromide (EVBr2), pyridinium tribromide (PHBP), 2,4,6-tribromophenol, tetrabutylammonium bromide (TBABr), N-ethylpyridinium bromide (EPYBr), N-butylpyridinium bromide (BPYBr) and N-hexylpyridinium bromide (HPYBr) as well as a mixed halogen compound tetra-n-butylammonium dibromide iodide.

[0012] Preferably, the two-dimensional transition metal carbide / boride with halogen terminal groups includes I-MXene, Br-MXene, I-MBene, Br-MBene, and two-dimensional layered compounds containing mixed halogens I-Br-MXene, I-Br-MBene (wherein the general formula of MXene is M n+1 X n T xIt is composed of n+1 layers of transition metal M and n layers of X elements (carbon, nitrogen, phosphorus or boron) arranged alternately. x That is, the terminal functional group on the surface of the M atomic layer).

[0013] Preferably, the halogen-containing ionic liquid includes 1-hexyl-3-methylimidazolium iodide, 1-hexyl-3-methylimidazolium bromide, 1-aminopropyl-3-methyl bromide, and 1,4-di(methylimidazolium)butane dibromide.

[0014] Preferably, the conductive agent includes one of acetylene black, conductive carbon black, conductive carbon nanotubes, conductive graphite, a composite conductive agent, graphene and Ketjen black.

[0015] Preferably, the conductive carbon black is Superi P Li.

[0016] Preferably, the binder includes one of sodium carboxymethyl cellulose CMC-Na, polytetrafluoroethylene PTFE, polyvinylidene fluoride PVDF, styrene-butadiene rubber SBR emulsion, polyimide PI, polyacrylic acid PAA, polyacrylonitrile PAN, polyvinyl alcohol PVA, Nafion membrane solution, polyacrylate, chitosan and sodium alginate; the binder is dispersed in a dispersing solvent, and the dispersing solvent includes one of N-methylpyrrolidone (NMP), water, and an acetic acid aqueous solution with a concentration of 1%.

[0017] Preferably, the current collector comprises one of hydrophobic carbon cloth, hydrophilic carbon cloth, carbon paper, titanium mesh, carbon felt, stainless steel mesh, titanium sheet, aluminum foil, foam copper, foam nickel, foam silver, conductive resin and titanium-nickel alloy current collector.

[0018] Preferably, the positive electrode plate is obtained by mixing a positive electrode halogen active substance, a conductive agent, and a binder to obtain a mixture, and the mixture is uniformly formed into a slurry and then coated on a current collector with a thickness of 0.1-5 mm, and dried in a vacuum oven, and finally cut into electrode sheets to serve as the positive electrode of the battery; wherein the mass fraction of the positive electrode halogen active substance accounts for 5%-95% of the total mass of the above-mentioned mixture, the mass fraction of the conductive agent accounts for 5%-90% of the total mass of the above-mentioned mixture, and the mass of the binder accounts for 0%-30% of the total mass of the above-mentioned mixture.

[0019] Preferably, the metal salt of the static halogen battery is used as a supporting electrolyte, and water and / or an organic electrolyte is used as an electrolyte solvent.

[0020] Preferably, the chloride ionic liquid is composed of organic cations and anions, wherein the cations include: pyridinium cations, quaternary ammonium cations, quaternary phosphonium cations, imidazolium cations, quaternary phosphonium cations and piperidine cations, and the anions are chloride ions.

[0021] Preferably, the cations in the chloride ionic liquid include: pyridinium cations, quaternary ammonium cations, ammonium cations, imidazolium cations, quaternary phosphonium cations and piperidinium cations. The specific chemical structural formula of the cations is as follows:

[0022]

[0023] Among them, R1, R2, R3, and R4 refer to alkyl chains C at different substitution positions. n , n represents the number of carbons in the alkyl chain of the substituent R, n = 2 to 16;

[0024] The chloride ion liquid comprises at least one chloride salt selected from the following ionic liquids as a chloride ion source of the additive: a chloride salt composed of a pyridinium cation and a chloride anion, a chloride salt composed of a quaternary phosphonium cation and a chloride anion, a chloride salt composed of an imidazolium cation and a chloride anion, and a chloride salt composed of a piperidine cation and a chloride anion. The total chloride ion concentration provided by the chloride ion liquid in the electrolyte is 0.001-30 mol kg -1 .

[0025] Preferably, the chloride salts composed of pyridinium cations and chloride anions include: N-ethylpyridinium chloride (EPyCl), propylpyridinium chloride (PPyCl), N-butylpyridinium chloride (BPyCl);

[0026] Chloride salts composed of pyrrole cations and chloride anions include: N-ethyl-N-methylpyrrolidine chloride (Py 12 Cl), N-propyl-N-methylpyrrolidine chloride (Py 13 Cl), N-butyl-N-methylpyrrolidine chloride (Py 14 Cl), N-allyl-N-methylpyrrolidino chloride (Py 1A Cl);

[0027] Chloride salts composed of quaternary ammonium cations and chloride anions include: tetramethylammonium chloride (N 1111 Cl), propyltrimethylammonium chloride (N 3111 Cl), butyltrimethylammonium chloride (N 4111 Cl), hexyltrimethylammonium chloride (N 6111 Cl), triethylmethylammonium chloride (N 2221 Cl), tributyl methyl ammonium chloride (N 4441Cl), trioctylmethylammonium chloride (N 8881 Cl), tetraethylammonium chloride (N 2222 Cl), tetrapropylammonium chloride (N 3333 Cl), tetrabutylammonium chloride (N 4444 Cl);

[0028] Chloride salts composed of quaternary phosphonium cations and chloride anions include: methyltributylphosphonium chloride (P 1444 Cl), tetrabutylphosphonium chloride (P 4444 Cl), hexyltributylphosphonium chloride (P 6444 Cl), octyltributylphosphonium chloride (P 8444 Cl), tetradecyl tributyl phosphonium chloride (P 14444 Cl);

[0029] Chloride salts composed of imidazolium cations and chloride anions include: 1-ethyl-3-methylimidazolium chloride (EMimCl), 1-butyl-3-methylimidazolium chloride (BMimCl), 1-hexyl-3-methylimidazolium chloride (HMimCl), 1-octyl-3-methylimidazolium chloride (OMimCl), 1-decyl-3-methylimidazolium chloride (DMimCl), 1-dodecyl-3-methylimidazolium chloride (C 12 MimCl), 1-tetradecyl-3-methylimidazolium chloride (C 14 MimCl), 1-hexadecyl-3-methylimidazolium chloride (C 16 MimCl);

[0030] Chloride salts composed of piperidine cations and chloride anions include: N-ethyl-N-methylpiperidinium chloride (PP 12 Cl), N-butyl-N-methylpiperidinium chloride (PP 14 Cl).

[0031] Preferably, the supporting electrolyte in the electrolyte includes: zinc sulfate, zinc perchlorate, bis(trifluoromethylsulfonyl)imide zinc, zinc trifluoromethanesulfonate, zinc tetrafluoroborate, zinc acetate, zinc gluconate, zinc citrate, zinc fluoride, zinc chloride, zinc bromide, zinc iodide, provided as a zinc ion source; the supporting electrolyte in the electrolyte includes: bis(trifluoromethylsulfonyl)imide lithium, lithium trifluoromethanesulfonate, lithium hexafluorophosphate, lithium tetrafluoroborate, bis(trifluorosulfonyl)imide lithium salt, lithium nitrate, lithium bis(oxalate)borate, lithium difluorooxalateborate, lithium chloride, any one or more of lithium ion sources The electrolyte comprises: a supporting electrolyte comprising: sodium bis(trifluoromethylsulfonyl)imide, sodium trifluoromethanesulfonate, sodium hexafluorophosphate, sodium trifluoromethanesulfonate, sodium perchlorate, sodium tetrafluoroborate, sodium nitrate, and sodium chloride as a sodium ion source; a supporting electrolyte comprising: potassium bis(trifluoromethylsulfonyl)imide, potassium bis(trifluoromethylsulfonyl)imide, potassium hexafluorophosphate, potassium perchlorate, potassium trifluoromethanesulfonate, and potassium chloride as a potassium ion source; and a metal salt ion concentration range of the supporting electrolyte in the electrolyte is 0.001-30 mol kg -1 .

[0032] Preferably, the electrolyte solvent in the electrolyte includes one of water and an organic solvent or a mixture of two thereof, and the organic solvent includes one or more of ethanol, acetonitrile (ACN), dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), propylene carbonate (PCA), ethyl methyl carbonate (CMC), ethylene carbonate (EC), dimethyl carbonate (DMC), vinylene carbonate (VC), methyl propionate (MP), fluoroethylene carbonate (FEC), dimethoxyethane (DME), and 1,3-dioxolane (DOL).

[0033] Preferably, the negative electrode includes a metal foil and a non-foil negative electrode material, and the non-foil negative electrode material includes one of zinc powder, lithium powder, graphite, hard carbon, MXene, 3,4,9,10-tetracarboxylic acid diimide (PTCDI), perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA), lithium phthalate, and 9,10-anthraquinone (9,10-AQ).

[0034] Preferably, the negative electrode comprises a negative electrode halogen active substance, a conductive agent, a binder and a current collector; the negative electrode pole piece is obtained by mixing the negative electrode halogen active substance, the conductive agent and the binder to obtain a mixture II, and the mixture II is uniformly formed into a slurry and then coated on a current collector with a thickness of 0.1-5 mm, and dried in a vacuum oven, and finally cut into electrode sheets to serve as the negative electrode of the battery; wherein the mass fraction of the negative electrode halogen active substance accounts for 5%-95% of the total mass of the above-mentioned mixture II, the mass fraction of the conductive agent accounts for 5%-90% of the total mass of the above-mentioned mixture II, and the mass fraction of the binder accounts for 0%-30% of the total mass of the above-mentioned mixture II; the conductive agent, the binder and the current collector in the negative electrode pole piece are consistent with the raw materials used in the preparation process of the positive electrode pole piece.

[0035] Preferably, the diaphragm includes one or more of a glass fiber diaphragm, a polypropylene (PP) diaphragm, a polyethylene (PE) microporous diaphragm, a polyimide (PI) diaphragm, a perfluorosulfonic acid membrane, a porous polyolefin diaphragm, and an aramid diaphragm.

[0036] Preferably, the diaphragm is a glass fiber diaphragm.

[0037] Preferably, the packaging materials include: stainless steel button battery shell, aluminum metal battery shell, titanium metal battery shell, soft-pack aluminum-plastic film, plastic battery shell, and cylindrical steel shell.

[0038] The beneficial effects of the present invention are:

[0039] 1. The static halogen battery provided by the present invention uses chloride ion liquid as an electrolyte additive to stably generate high-valent halogen ions I + and / or Br + , and successfully achieved the reversible transformation of high-valent halogen ions in a variety of electrolyte systems; compared with the more traditional single-electron mechanism halogen battery, under the multi-electron transfer mechanism ( and / or The discharge platform, discharge capacity and energy density of halogen batteries can be doubled, especially those with higher discharge platform. (1.27V vs.SHE) bromine battery system significantly optimizes the battery's energy output characteristics.

[0040] 2. The static halogen battery provided by the present invention uses chloride ion liquid as an electrolyte additive, which greatly increases the chloride ion concentration in the aqueous / organic electrolyte compared with traditional inorganic chloride salts;

[0041] 3. The static halogen battery provided by the present invention uses chloride ionic liquid as an electrolyte additive, and the electrolyte additive has green and mild characteristics. Among them, the organic cations in the ionic liquid can protect the negative electrode metal, inhibit the growth of metal dendrites, and stabilize the negative electrode structure. Even in aqueous, organic, and aqueous-organic hybrid static halogen batteries with higher concentrations of additives, it can still stably play the role of stabilizing high-valent halogen ions without corroding the battery packaging components. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 The electrolyte (1 mol kg -1 ZnSO4+0.5mol kg -1 HMimCl) assembled zinc-iodine battery and the electrolyte in Comparative Example 1 (1 mol kg -1 The zinc-iodine battery assembled with ZnSO4) at 5mV s -1 Cyclic voltammetry scanning curve at scanning speed;

[0043] Figure 2 The electrolyte (1 mol kg -1 ZnSO4+0.5mol kg -1 The zinc-iodine battery assembled with HMimCl) was tested at 0.5-10A g -1 Rate performance curve under current density;

[0044] Figure 3 The electrolyte (1 mol kg -1 ZnSO4+0.5mol kg -1 HMimCl) assembled zinc-iodine battery at 1A g -1 Cyclic performance curve under current density;

[0045] Figure 4 The electrolyte (1 mol kg -1 ZnSO4+0.5mol kg -1 HMimCl) assembled zinc-iodine battery at 1A g -1 Constant current charge and discharge diagram under current density and its corresponding in-situ Raman spectrum;

[0046] Figure 5 The electrolyte (30 mol kg -1 The zinc-iodine battery assembled with ZnCl2 at 5mV s -1 Cyclic voltammetry scanning curve at scanning speed;

[0047] Figure 6The electrolyte (2 mol kg -1 ZnSO4+0.05mol kg -1 C 12 The Zn-Zn symmetric battery assembled with MimCl) at 1 mA cm -2 Current density, 1mAh cm -2 Long cycle test curve at cut-off capacity;

[0048] Figure 7 is the electrolyte (3 mol kg -1 Zn(OTf)2+2.5mol kg -1 OMimCl) assembled zinc-bromine battery and the electrolyte in comparative example 3 (3 mol kg -1 Zn(OTf)2 electrolyte) at 1A g -1 Constant current charge and discharge curve under current density;

[0049] Figure 8 is the electrolyte (3 mol kg -1 Zn(OTf)2+2.5mol kg -1 OMimCl) assembled zinc-bromine battery at 1-10A g -1 Rate performance curve under current density;

[0050] Fig. 9 is the electrolyte (3 mol kg -1 Zn(OTf)2+2.5mol kg -1 OMimCl) assembled zinc-bromine battery at 7A g -1 Cyclic performance curve under current density;

[0051] Fig.10 is the electrolyte (3 mol kg -1 Zn(OTf)2+2.5mol kg -1 OMimCl) assembled zinc-bromine battery at 1A g -1 In-situ Raman spectra under current density;

[0052] Fig.11 The electrolyte (1 mol L -1 LiTFSI, 0.2 mol L -1 LiNO3 and 1 mol L -1 The lithium-bromine battery assembled with 1-ethyl-3-methylimidazolium chloride (EMimCl) dissolved in DOL:DME organic solvent with a volume ratio of 1:1 was tested at 5 mV s -1Cyclic voltammetry scanning curve at a scan rate of . DETAILED DESCRIPTION

[0053] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0054] In order to make the purpose and technical solution of the present invention clearer, the specific embodiments are further classified and explained below, and the explanation is combined with the diagrams. This embodiment specifically uses different halogen source positive electrode materials; electrolyte systems with different concentrations and solvents; different negative electrodes; and different battery components to assemble the battery. Among them, the battery assembly process is a conventional technical means in the field, and can be reasonably optimized according to actual operation needs. The static halogen battery is 25

[0055] The constant temperature test was carried out in a constant temperature box at ℃.

[0056] Example 1: The positive electrode material used in this example is tin tetraiodide (SnI4). The active material (SnI4), the conductive agent (acetylene black) and the binder (PVDF) are fully mixed in the dispersion NMP at a mass ratio of 7:2:1 for four hours, and then evenly coated on the conductive current collector stainless steel mesh, and then vacuum dried at 80°C for 24 hours to obtain a positive electrode with a unit area loading of 2 mg cm -2 The positive electrode sheet; the electrolyte is 1 mol kg -1 ZnSO4+0.5mol kg -1 1-Hexyl-3-methylimidazolium chloride (HMimCl); the negative electrode uses zinc foil with a thickness of 100 μm; the positive and negative electrodes are separated by a glass fiber separator and assembled into a button CR 2032 zinc-iodine battery.

[0057] Figure 1 The zinc-iodine battery composed of the above electrolyte was subjected to a scan rate of 5 mV s -1 , the cyclic voltammetry scanning test result curve with a cut-off voltage interval of 0.8-1.9V. As shown in the figure, the solid line curve is the test result of the assembled battery in Example 1, and there are two pairs of redox peaks. Among them, the two reduction peaks correspond to the following reactions during discharge:

[0058] Positive electrode: I + +e - →I 0 (1.76V vs.Zn 2+ / Zn)

[0059] I 0 +e - →I - (1.29V vs.Zn2+ / Zn);

[0060] Anode: Zn-2e - →Zn 2+

[0061] Compared with the redox peak in the traditional single-electron conversion system, the newly emerging redox peak in the multi-electron conversion mechanism has a narrow half-peak width and a strong current response, which means that the new reaction initiated by ionic liquids has excellent reaction kinetics and high reversibility. Figure 2 A zinc-iodine battery according to Example 1 is provided at a current density of 0.5-10A. -1 The rate performance results are shown in the curve diagram, as shown in the results, at 10A g -1 The capacity of the battery is still 200mAh g -1 , and has good rate performance. Figure 3 A zinc-iodine battery according to Example 1 is provided at a current density of 1A g -1 The cycle performance test result curve at a cut-off voltage of 0.8-1.9V shows that the capacity is 312mAh g based on the iodine source as the active mass calculation formula. -1 At 1A g -1 After 4000 cycles, the capacity retention rate is still above 70%, showing outstanding cycle stability. In order to further reveal the dynamic changes of the iodine source in the reaction process, the positive electrode, electrolyte and negative electrode described in Example 1 are matched and assembled in an in-situ Raman battery mold for in-situ Raman test characterization. The in-situ Raman battery is charged and discharged using a constant current charge and discharge test method. Figure 4 The Raman spectra of the different charge states during the charge and discharge process are shown. When the charge is 1.3V, the spectrum is at 170cm -1 A strong peak signal is provided at I3 - The characteristic peak of the species, that is, I 0 After the species is generated, it quickly - Combine to generate I3 - As the voltage increases further, I3 - The signal weakens and is replaced by 422cm -1 and 840cm -1 The signal peak at the position is enhanced, proving that I + The generation of species. This law shows an opposite trend during discharge, and the entire multi-electron conversion mechanism process shows the advantage of high reversibility.

[0062] Comparative Example 1: The electrolyte used in this comparative example is 1 mol kg -1 ZnSO4, the remaining steps are the same as in Example 1. Figure 1As shown by the dashed line in the middle, the assembled zinc-iodine battery has a high charge / discharge rate at 5 mV s -1 In the cyclic voltammetry scanning curve at a scan rate of 1.43 / 1.25 V, there is only a pair of standard reversible redox peaks. That is, in the absence of chloride ions, the iodine source can only present a single electron I in the electrochemical process. - / I 0 The zinc-iodine battery composed of the electrolyte described in Comparative Example 1, due to the lack of chloride salt additives, I 0 It is impossible to further stably form high-valent halogen ions. Therefore, the specific capacity calculated based on the iodine source mass as the active mass is only 135 mAh g -1 In Example 1, the reversible conversion reaction of the valence state of iodine between -1 to 0 and 0 to +1 is achieved through the activation of the organic chloride salt and the stabilization of the high-valent halogen. The capacity provided by the battery system with a multi-electron conversion mechanism is twice the discharge capacity based on the single-electron system.

[0063] Comparative Example 2: The electrolyte used in this comparative example is 30 mol kg -1 ZnCl2, and the remaining steps are the same as in Example 1. Figure 5 The cyclic voltammetry of zinc-iodine battery with high concentration of inorganic chloride salt as additive is given. -1 At a scan rate of , the zinc-iodine battery produced severe polarization when it was scanned forward to 1.9V, resulting in a cross-curve in the negative scan, and a large and abnormally high current response fluctuation, indicating that the high concentration of inorganic salts was seriously reacting with the commercial stainless steel battery shell. Therefore, it is impossible to achieve reversible conversion of positively charged halogen ions using conventional battery shells under high concentrations of inorganic chloride salts.

[0064] Example 2: The electrolyte used in this example is 2 mol kg -1 ZnSO4+0.05mol kg -1 1-Dodecyl-3-methylimidazolium chloride (C 12 MimCl); 200 μm thick zinc foil was used as the positive electrode and the negative electrode; the positive electrode and the negative electrode were separated by a glass fiber separator and assembled into a button CR 2032 zinc-zinc symmetrical battery. Figure 6 The results show that the symmetric cell with a chloride ion solution as an electrolyte has a charge and discharge rate of 1 mA cm -2 The current density is 1 mAh cm -2 The long cycle test chart. The test results show that during the 850 cycles, the symmetrical battery can work stably for 1700 hours, indicating that the addition of chloride ion liquid has a significant protective effect on alleviating negative electrode corrosion and inhibiting dendrite growth.

[0065] Example 3: This example uses the drop coating evaporation method to prepare the positive active electrode, and the conductive current collector is a hydrophobic carbon cloth with a concentration of 1 mg cm -2 Weigh a certain amount of activated carbon YP 80, and fully mix YP80, acetylene black and PVDF in NMP at a mass ratio of 8:1:1 for four hours, evenly apply it on the conductive substrate, and vacuum dry it at 100°C for 24 hours. The obtained carbon adsorption substrate is cut into electrode discs with a diameter of 12 mm for standby use; the positive electrode active material pyridinium tribromide (PHBP) is dissolved in ethanol and configured to 0.05 mol L -1 A uniform solution of 2.3 mg of PHBP solution was pipetted with a pipette and evenly coated on a 12 mm carbon adsorption substrate electrode, and then vacuum dried at 40 °C for 12 h to obtain a unit area loading of 2 mg cm -2 The positive electrode sheet; the electrolyte is 3 mol kg -1 Zn(OTf)2+2.5mol kg -1 1-Octyl-3-methylimidazolium chloride (OmimCl); a zinc foil with a thickness of 200 μm was used as the negative electrode; and a button CR 2032 zinc-bromine battery was assembled.

[0066] Figure 7 The zinc-bromine battery composed of the electrolyte in this embodiment is at a current density of 1Ag -1 , the charge and discharge test result curve with a cut-off voltage of 1.2-2.1V. As shown in the figure, the curve has two discharge platforms, corresponding to the discharge:

[0067] Positive electrode: Br + +e - →Br 0 (1.9V vs.Zn 2+ / Zn)

[0068] Br 0 +e - →Br - (1.7V vs.Zn 2+ / Zn);

[0069] Negative electrode: Zn 0 -2e - →Zn 2+

[0070] As shown by the solid line for the multi-electron conversion system, the newly added 1.9V platform can provide an additional 138% energy output. The energy output of the multi-electron system proposed in this embodiment is about 2.38 times that of the single-electron system. Figure 8 A zinc-bromine battery according to Example 3 is provided at a current density of 0.5-10A g-1 The rate performance results are shown in the curve diagram, as shown in the results, at 1A g -1 The capacity of the lower battery is still 530mAh g -1 , the Coulombic efficiency is as high as 71.6%. -1 The capacity of the battery remains at 295mAh g -1 , proving that the multi-electron zinc-bromine system in Example 3 exhibits good rate performance. Fig. 9 A zinc-bromine battery according to Example 3 is provided at a current density of 7A g -1 The cycle performance test result curve at a cut-off voltage of 1.2-2.1V shows that after 2000 cycles, the capacity is still 202mAh g -1 , and the coulombic efficiency is as high as 96%, and it shows outstanding cycle stability. In order to further reveal the dynamic changes of the bromine source in the reaction process, the positive electrode, electrolyte and negative electrode described in Example 3 are matched and assembled in an in-situ Raman battery mold for in-situ Raman test characterization. The in-situ Raman battery is charged and discharged using a constant current charge and discharge test method. Fig.10 The Raman spectra of the different charge states during the charge and discharge process are shown. When the charge is 1.8V, the spectrum is at 180cm -1 A strong peak signal is provided at Br 0 As the voltage increases further, at 260cm -1 The signal peak at gradually increased, proving that Br + The generation of species. This law shows an opposite trend during discharge, and the entire two-electron conversion mechanism process shows the advantage of high reversibility.

[0071] Comparative Example 3: This comparative example uses 3 mol kg -1 Zn(OTf)2 was used as the electrolyte, and the remaining steps were the same as those in Example 3. Figure 7 As shown by the dashed line, the zinc-bromine battery composed of the electrolyte described in Comparative Example 3 is -1 In the constant current charge and discharge test under the condition of current density and cut-off voltage of 1.2-2.1V, there is only a discharge platform at 1.75V, corresponding to Br 0 / Br - That is, in the absence of chloride ions, the bromine source can only present a single-electron Br in the electrochemical process. - / Br 0 In the absence of chloride ions, Br 0 It is impossible to further form a stable high-valent halogen ion Br + Therefore, the specific capacity calculated based on the bromine source mass as the active mass is only 237 mAh g -1In Example 3, the reversible conversion reaction of the valence state of bromine between -1 to 0 and 0 to +1 is achieved through the activation of the organic chloride salt and the stabilization of the high-valent halogen. The capacity provided by the battery system with a multi-electron conversion mechanism is nearly twice the discharge capacity based on the single-electron system.

[0072] Example 4: The conductive current collector used in this example is aluminum foil. Ethyl viologen dibromide (EVBr2), Super P Li and PVDF are uniformly mixed in a mass ratio of 8:1:1, and then the binder dispersion NMP is slowly dripped and ground into a uniform slurry. The mixed slurry is evenly coated on a 500μm titanium foil and dried in a vacuum drying oven at 100℃ for 24 hours to obtain a unit area loading of 2mg cm -2 The positive electrode sheet is 300 μm thick lithium foil for the negative electrode; the electrolyte is 1 mol L -1 LiTFSI, 0.2 mol L -1 LiNO3 and 1 mol L -1 1-Ethyl-3-methylimidazolium chloride (EmimCl) was dissolved in a DOL:DME organic solvent with a volume ratio of 1:1; a commercial Celgard 2400 polypropylene separator with a thickness of 20 μm was used to separate the positive and negative electrodes, and finally assembled into a button CR 2032 lithium-bromine battery. Fig.11 As shown by the solid line in the middle, the lithium-bromine battery composed of the electrolyte described in Example 4 is at 5mV s -1 In the cyclic voltammetry test under the condition of current density and cutoff voltage of 1.8-3.9V, the reaction based on bromine source showed two obvious redox peaks at 3.3V and 3.7V, corresponding to Br 0 / Br - and Br + / Br 0 reaction process.

[0073] Example 5: This example uses ruthenium triiodide (RuI3) as the positive electrode active material, and its preparation process is the same as that of Example 1; the electrolyte uses 5 mol kg -1 Zn(BF4)2+10mol kg -1 Triethylmethylammonium chloride (N 2221 Cl); zinc powder, acetylene black and chitosan were mixed evenly in a mass ratio of 5:4:1, and then 1% acetic acid aqueous solution was slowly added, and after stirring for four hours, it was coated on a 50μm copper foil and dried in a vacuum oven at 80°C for 12 hours to obtain a negative electrode sheet; a zinc-iodine battery was assembled using a Swagelok battery.

[0074] Example 6: The electrolyte of this example is 0.5 mol L -11-Tetradecyl-3-methylimidazolium chloride (C 14 mimCl) and 1 mol L -1 NaPF6 is dissolved in a commercial organic electrolyte having a volume ratio of DME:DOL of 1:1; a sodium metal sheet is used as the negative electrode; the other steps are the same as those in Example 5, and a sodium-iodine battery is assembled using button cells containing an aluminum coating.

[0075] Example 7: In this example, iodine monobromide (IBr), Super P Li and PVDF are uniformly mixed in a mass ratio of 8:1:1, and then the binder dispersion NMP is slowly dropped and ground into a uniform slurry, and finally coated on a 500μm titanium foil and dried in a vacuum drying oven at 80°C for 12 hours to obtain a positive electrode sheet; the commercial use of the negative electrode and the electrolyte is the same as in Example 6, and a sodium-iodine / bromine hybrid battery is assembled using a button cell containing an aluminum coating.

[0076] To facilitate comparison of the working contents of each embodiment and the comparative example, the relevant parameters and performances are shown in the following table:

[0077]

[0078] The present invention introduces mild green chloride ionic liquid as electrolyte additive to realize the halogen battery in aqueous electrolyte, organic electrolyte and aqueous-organic hybrid electrolyte system based on I - / I 0 / I + and / or Br - / Br 0 / Br + The electrolyte provided by the present invention provides a higher output voltage, discharge capacity, energy density, and corrosion resistance for a static halogen battery in a multi-system.

[0079] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A static halogen battery based on a multi-electron transfer mechanism, characterized in that: The halogen battery comprises a positive electrode, an electrolyte, a negative electrode, a separator and a packaging material, wherein the electrolyte contains a chloride ion liquid as an additive.

2. The static halogen battery based on multi-electron transfer mechanism according to claim 1, characterized in that: The positive electrode includes a positive electrode halogen active material, a conductive agent, a binder and a current collector, wherein the positive electrode halogen active material includes: iodine element, bromine element, iodide and bromide and iodine / bromine mixed halide, wherein the positive electrode halogen active material includes one or more of inorganic halides, halogen-containing perovskite materials, organic molecular halides, two-dimensional transition metal carbides / borides of halogen terminal groups, and halogen-containing ionic liquids as iodine and / or bromine sources.

3. The static halogen battery based on multi-electron transfer mechanism according to claim 2, characterized in that: The conductive agent includes one of acetylene black, conductive carbon black, conductive carbon nanotubes, conductive graphite, a composite conductive agent, graphene and Ketjen black.

4. The static halogen battery based on multi-electron transfer mechanism according to claim 2, characterized in that: The binder comprises one of sodium carboxymethyl cellulose, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber emulsion, polyimide, polyacrylic acid, polyacrylonitrile, polyvinyl alcohol, Nafion membrane solution, polyacrylate, chitosan and sodium alginate; the binder is dispersed in a dispersion solvent, and the dispersion solvent comprises one of N-methyl pyrrolidone, water and 1% acetic acid aqueous solution.

5. The static halogen battery based on multi-electron transfer mechanism according to claim 2, characterized in that: The current collector comprises one of hydrophobic carbon cloth, hydrophilic carbon cloth, carbon paper, titanium mesh, carbon felt, stainless steel mesh, titanium sheet, aluminum foil, foam copper, foam nickel, foam silver, conductive resin and titanium-nickel alloy current collector.

6. The static halogen battery based on multi-electron transfer mechanism according to any one of claims 1 to 5, characterized in that: The positive electrode sheet is obtained by mixing a positive electrode halogen active material, a conductive agent, and a binder to obtain a mixture. The mixture is uniformly formed into a slurry and then coated on a current collector with a thickness of 0.1-5 mm, and dried in a vacuum oven. Finally, it is cut into electrode sheets to serve as the positive electrode of the battery; wherein the mass fraction of the positive electrode halogen active material accounts for 5%-95% of the total mass of the above-mentioned mixture, the mass fraction of the conductive agent accounts for 5%-90% of the total mass of the above-mentioned mixture, and the mass fraction of the binder accounts for 0%-30% of the total mass of the above-mentioned mixture.

7. The static halogen battery based on multi-electron transfer mechanism according to claim 1, characterized in that: The metal salt of the static halogen battery is used as a supporting electrolyte, and water and / or an organic electrolyte is used as an electrolyte solvent.

8. The static halogen battery based on multi-electron transfer mechanism according to claim 1, characterized in that: The chloride ionic liquid is composed of organic cations and anions, wherein the cations include: pyridinium cations, quaternary ammonium cations, quaternary phosphonium cations, imidazole cations, quaternary phosphonium cations and piperidine cations, and the anions are chloride ions; The chloride ion liquid comprises at least one chloride salt selected from the following ionic liquids as a chloride ion source of the additive: a chloride salt composed of a pyridinium cation and a chloride anion, a chloride salt composed of a quaternary ammonium cation and a chloride anion, a chloride salt composed of a quaternary phosphonium cation and a chloride anion, a chloride salt composed of an imidazole cation and a chloride anion, and a chloride salt composed of a piperidine cation and a chloride anion. The total chloride ion concentration provided by the chloride ion liquid in the electrolyte is 0.001-30 mol kg -1 .

9. The static halogen battery based on multi-electron transfer mechanism according to claim 7, characterized in that: The supporting electrolyte in the electrolyte includes: one or more of zinc sulfate, zinc perchlorate, bis(trifluoromethylsulfonyl)imide zinc, zinc trifluoromethanesulfonate, zinc tetrafluoroborate, zinc acetate, zinc gluconate, zinc citrate, zinc fluoride, zinc chloride, zinc bromide, and zinc iodide as a zinc ion source; the supporting electrolyte in the electrolyte includes: one or more of bis(trifluoromethylsulfonyl)imide lithium, lithium trifluoromethanesulfonate, lithium hexafluorophosphate, lithium tetrafluoroborate, bis(fluorosulfonyl)imide lithium salt, lithium nitrate, lithium bis(oxalate)borate, lithium difluorooxalateborate, and lithium chloride as a lithium ion source The supporting electrolyte in the electrolyte includes: any one or more of sodium bis(trifluoromethylsulfonyl)imide, sodium trifluoromethanesulfonate, sodium hexafluorophosphate, sodium trifluoromethanesulfonate, sodium perchlorate, sodium tetrafluoroborate, sodium nitrate, and sodium chloride as a sodium ion source; the supporting electrolyte in the electrolyte includes: any one or more of potassium bis(trifluoromethylsulfonyl)imide, potassium bis(trifluoromethylsulfonyl)imide, potassium hexafluorophosphate, potassium perchlorate, potassium trifluoromethanesulfonate, and potassium chloride as a potassium ion source; the metal salt ion concentration of the supporting electrolyte in the electrolyte is in the range of 0.001-30 mol kg -1 .

10. The static halogen battery based on multi-electron transfer mechanism according to claim 7, characterized in that: The electrolyte solvent in the electrolyte includes one of water and an organic solvent or a mixture of the two, and the organic solvent includes one or more of ethanol, acetonitrile, dimethyl sulfoxide, tetrahydrofuran, propylene carbonate, ethyl methyl carbonate, ethylene carbonate, dimethyl carbonate, vinylene carbonate, methyl propionate, fluoroethylene carbonate, dimethoxyethane, and 1,3-dioxolane.

11. The static halogen battery based on multi-electron transfer mechanism according to claim 1, characterized in that: The negative electrode includes one of a metal foil and a non-foil negative electrode material, and the non-foil negative electrode material includes one of zinc powder, lithium powder, graphite, hard carbon, MXene, 3,4,9,10-tetracarboxylic acid diimide, perylene-3,4,9,10-tetracarboxylic dianhydride, lithium phthalate, and 9,10-anthraquinone (9,10-AQ).

12. The static halogen battery based on multi-electron transfer mechanism according to claim 1, characterized in that: The negative electrode comprises a negative electrode halogen active material, a conductive agent, a binder and a current collector; the electrode sheet of the negative electrode is obtained by mixing the negative electrode halogen active material, the conductive agent and the binder to obtain a mixture II, the mixture II is uniformly formed into a slurry and then coated on a current collector with a thickness of 0.1-5 mm, and dried in a vacuum oven, and finally cut into electrode sheets to serve as the negative electrode of the battery; wherein the mass fraction of the negative electrode halogen active material accounts for 5%-95% of the total mass of the above-mentioned mixture II, the mass fraction of the conductive agent accounts for 5%-90% of the total mass of the above-mentioned mixture II, and the mass fraction of the binder accounts for 0%-30% of the total mass of the above-mentioned mixture II.

13. The static halogen battery based on multi-electron transfer mechanism according to claim 1, characterized in that: The diaphragm includes one or more of a glass fiber diaphragm, a polypropylene diaphragm, a polyethylene microporous diaphragm, a polyimide diaphragm, a perfluorosulfonic acid membrane, a porous polyolefin diaphragm, and an aramid diaphragm.

14. The static halogen battery based on multi-electron transfer mechanism according to claim 1, characterized in that: The packaging materials include: stainless steel button battery shell, aluminum metal battery shell, titanium metal battery shell, soft-pack aluminum-plastic film, plastic battery shell, and cylindrical steel shell.

Citation Information

Patent Citations

  • Organic lithium-iodine battery based on two-electron transfer mechanism as well as manufacturing method and application of organic lithium-iodine battery

    CN116264316A

  • Four-electron conversion reaction-based aqueous zinc-iodine battery and electrolyte thereof

    WO2021228001A1

Cited By

  • Aqueous zinc-iodine battery electrolyte and preparation method and application thereof

    CN121790544A